2014
DOI: 10.1016/j.stem.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

NANOG and CDX2 Pattern Distinct Subtypes of Human Mesoderm during Exit from Pluripotency

Abstract: Mesoderm is induced at the primitive streak (PS) and patterns subsequently into mesodermal subtypes and organ precursors. It is unclear whether mesoderm induction generates a multipotent PS progenitor or several distinct ones with restricted subtype potentials. We induced mesoderm in human pluripotent stem cells with ACTIVIN and BMP or with GSK3-β inhibition. Both approaches induced BRACHYURY(+) mesoderm of distinct PS-like identities, which had differing patterning potential. ACTIVIN and BMP-induced mesoderm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
194
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(212 citation statements)
references
References 40 publications
18
194
0
Order By: Relevance
“…Unexpectedly, the pluripotency marker NANOG was repressed upon MSX2 depletion in both H1 and H9 hESCs (Supplementary information, Figure S3A-S3D). We speculated that this might be related to NANOG function in suppressing neural differentiation and in patterning different subtypes of mesoderm cells after exit of hESCs from pluripotency, as described previously [41,42]. To further confirm the role of MSX2 in hESC early differentiation and exclude the potential ambiguity brought by shRNAs, we deleted MSX2 gene in hESCs using CRISPR-CAS9 technology.…”
Section: Msx2 Is Required For Hpscs' Exit From Pluripotency and Entrymentioning
confidence: 82%
“…Unexpectedly, the pluripotency marker NANOG was repressed upon MSX2 depletion in both H1 and H9 hESCs (Supplementary information, Figure S3A-S3D). We speculated that this might be related to NANOG function in suppressing neural differentiation and in patterning different subtypes of mesoderm cells after exit of hESCs from pluripotency, as described previously [41,42]. To further confirm the role of MSX2 in hESC early differentiation and exclude the potential ambiguity brought by shRNAs, we deleted MSX2 gene in hESCs using CRISPR-CAS9 technology.…”
Section: Msx2 Is Required For Hpscs' Exit From Pluripotency and Entrymentioning
confidence: 82%
“…These studies identified BMP signaling as a key requirement for hematopoietic progenitor specification and they established the role of Wnt signaling for mesoderm induction in vitro (Chadwick et al, 2003;Gadue et al, 2006;Johansson and Wiles, 1995;Kattman et al, 2011;Lindsley et al, 2006;Nakanishi et al, 2009;Yang et al, 2008;Zhang et al, 2008). More recent studies have shown that treatment of PSCs with activin favors the differentiation of anterior primitive streak derivatives such as endoderm, whereas treatment with BMP triggers the differentiation of posterior streak derivatives such as lateral plate and extraembryonic mesoderm (Bernardo et al, 2011;Mendjan et al, 2014). Differentiation of late primitive streak that generates paraxial mesoderm could be achieved by treating PSCs first with activin, FGF and PI3K inhibitors to induce anterior primitive streak fate and then with GSK3 inhibitors (to activate Wnt signaling) and FGF to recapitulate the late primitive streak environment (Mendjan et al, 2014).…”
Section: Primitive Streak and Mesoderm Induction In Vitromentioning
confidence: 99%
“…More recent studies have shown that treatment of PSCs with activin favors the differentiation of anterior primitive streak derivatives such as endoderm, whereas treatment with BMP triggers the differentiation of posterior streak derivatives such as lateral plate and extraembryonic mesoderm (Bernardo et al, 2011;Mendjan et al, 2014). Differentiation of late primitive streak that generates paraxial mesoderm could be achieved by treating PSCs first with activin, FGF and PI3K inhibitors to induce anterior primitive streak fate and then with GSK3 inhibitors (to activate Wnt signaling) and FGF to recapitulate the late primitive streak environment (Mendjan et al, 2014). Alternatively, by treating both mouse and human PSCs with BMP and Wnt activators sequentially, several groups were able to generate paraxial mesoderm progenitors (Chal et al, 2015;Mendjan et al, 2014;Sakurai et al, 2009Sakurai et al, , 2012.…”
Section: Primitive Streak and Mesoderm Induction In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Activin signaling has been shown to regulate both self-renewal and mesendoderm-endoderm differentiation of human embryonic stem cells (3,36,38,39,42,46). At low activin dose, Smad2 facilitates pluripotency of human embryonic stem cells by directly regulating NANOG expression (46) or by interacting with OCT4 to form a complex with TEAD to regulate expression of pluripotency genes (47).…”
Section: H3k27me3 Reduction Initiates Esc Mesendoderm Differentiationmentioning
confidence: 99%